Dampak Menonton Televisi Terhadap Prestasi Belajar Siswa Kelas V SDN No 80/1 Rengas Condong - A Admizal; Devi Novita Sari (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to describe the impact of watching television on the learning achievement of fifth grade students at SDN No 80/1 Rengas Condong. This type of research is a qualitative descriptive study to obtain information about the impact of watching television on student achievement in class V.B SDN No 80/1 Rengas Condong. This research was conducted at SDN No 80/1 Rengas Condong, Muara Bulian Subdistrict, Batanghari District, in V.B class students, which amounted to 24 students consisting of 11 women and 13 men. For this reason, researchers used a data collection tool using observations, interviews and questionnaires distributed to 24 students of class V.B SDN 80/1 Rengas Condong. Based on the results of research and discussion it can be concluded that watching television can reduce student learning achievement because students watch more television than learning. Students watch television in search of entertainment instead of seeking information / knowledge. And students watch television at the time of study, which is between 7:00 p.m. and 9:00 p.m. Watching television shows can have a detrimental effect on the decline in student learning performance because of the reduced frequency of learning at home to repeat the lessons students get at school.